Disturbance of the OPG/RANK/RANKL pathway and systemic inflammation in COPD patients with emphysema and osteoporosis - Bai Peng; Sun Yongchang; Jin Jianmin; Hou Jia; Li Ran; Zhang Qing; Wang Yang (Respiratory Research, 2011)
Abstract Background Osteoporosis is one of the systemic features of COPD. A correlation between the emphysema phenotype of COPD and reduced bone mineral density (BMD) is suggested by some studies, however, the mechanisms underlying this relationship are unclear. Experimental studies indicate that IL-1β, IL-6 and TNF-α may play important roles in the etiology of both osteoporosis and emphysema. The OPG/RANK/RANKL system is an important regulator of bone metabolism, and participates in the development of post-menopausal osteoporosis. Whether the OPG/RANK/RANKL pathway is involved in the pathogenesis of osteoporosis in COPD has not been studied. Methods Eighty male patients (current or former smokers) completed a chest CT scan, pulmonary function test, dual x-ray absorptiometry measurements and questionnaires. Among these subjects, thirty patients with normal BMD and thirty patients with low BMD were selected randomly for measurement of IL-1β, IL-6, TNF-α (flow cytometry) and OPG/RANK/RANKL (ELISA). Twenty age-matched healthy volunteers were recruited as controls. Results Among these eighty patients, thirty-six had normal BMD and forty-four had low BMD. Age, BMI and CAT score showed significant differences between these two COPD groups (p < 0.05). The low-attenuation area (LAA%) in the lungs of COPD patients was negatively correlated with lumbar vertebral BMD (r = 0.741; p < 0.0001). Forward logistic regression analysis showed that only LAA% (p = 0.005) and BMI (p = 0.009) were selected as explanatory variables. The level of IL-1β was significantly higher in the COPD patients as compared to the normal controls (p < 0.05), but the difference between the two COPD groups did not reach significance. The levels of IL-6 and TNF-α among the three groups were significantly different (p < 0.05). The level of RANKL and the RANKL/OPG ratio were significantly higher in COPD patients with low BMD compared to those with normal BMD and the normal controls (p < 0.05), and correlated negatively with lumbar vertebral BMD, but positively with LAA%. Conclusions Radiographic emphysema is correlated with low BMD in current and former smokers with COPD. IL-1β, IL-6, TNF-α, and the osteoporosis-related protein system OPG/RANK/RANKL may have some synergetic effects on emphysema and bone loss in COPD.